Effects of working in the studied profession during a Master’s degree Nursing course on self-assessment of vocational preparation of students G - Gotlib, Joanna; Synowiec, Joanna (Polish Journal of Public Health, 2013)
Introduction. According to the National Qualification Framework (binding in Poland since the academic year 2012/2013), the analysis of self-assessment of students shall be one of mandatory components of evaluation of outcomes of education. Aim. The aim of the study was to analyse the self-assess-ment of nursing students of WMU regarding their vocational preparation as well as to compare the self-assessment of students who have taken on employment in their profession and those who have not. Material and methods. A group of 573 nursing students of the Faculty of Health Science, WMU (74.4% of students); 39% of the first year students and 55% of the second year students; women: 96%. Group 1 (446 persons, 78%) comprised those ho were working as nurses; Group 2 (126 persons, 22%) included those who were not working as nurses. An anonymous, voluntary questionnaire developed by the authors, a personal-ized link to the questionnaire http://www.ankieter.pl/wypelnij/ankiete/id/5612/. A non-parametric statistical Mann-Whitney U test was used for statistical analysis (p<0.05). Results. The self-assessment of the students regarding their general professional and specific competences did not vary significantly between persons working and those not working in their profession (p=NS). Conclusions. Among the study group of students, taking on employment in the profession of a nurse did not influence the self-assessment of their vocational preparation or their professional competences. The self-assessment of vocational preparation among the study group of nursing students was high, which may be a sign that their expectations concern-ing the chosen major, curricula, and teaching content offered by the university were met and that the quality of teaching was high. Among the study group of nursing students, taking on employment in their profession during the studies did not decrease the self-assessment of the competences typical of the profession. This may be suggestive of sufficient vocational preparation acquired as early as during a Bachelor’s degree course.